(untitled) (Journal of Hama University, 2022)
Mouthwashes is one of the oral care methods, Herbal and natural mouthwashes are considered good alternatives to chemical-based mouthwashes, and because of this, interest in natural alternatives such as honey and propolis has increased, which have proven their effectiveness over time. The study aimed to study the effect of oral washes honey 50%, chlorhexidine 0.12% and propolis 5% on Streptococcus mutans and lactobacillus . The sample included 60 Syrian children (30 males - 30 females), between (6-12) years, a saliva swab was taken for each child Before oral washing with research materials and swab after oral rinsing using 10 ml of solution for 30 seconds, then cultivating it in the laboratory, Streptococcus mutans is grown on MSBA medium and lactobacilli on MRSA medium and conducting a count of the results and comparing the averages before and after and the effect of each substance on these bacteria. Results: The rate of decrease in the number of Streptococcus mutans was statistically significant after one minute of using chlorhexidine mouthwashes, which amounted to 89.97%,in propolis mouthwashes it was 85.49%, and in honey mouthwashes it was 76.29%. The rate of decrease in lactobacilli counts was statistically significant after one minute of using chlorhexidine mouthwashes, which amounted to 80.55%, in propolis mouthwashes it was 77.34%, and in honey mouthwashes it was 61.90%. Conclusion: This study demonstrated the efficacy of oral chlorhexidine, propolis and honey mouthwashes on streptococcus mutans and lactobacillus. Where the largest decrease effect was in chlorhexidine, then propolis, then honey.